2020
DOI: 10.1186/s12935-020-01501-7
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0000140 restrains the proliferation, metastasis and glycolysis metabolism of oral squamous cell carcinoma through upregulating CDC73 via sponging miR-182-5p

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a more common cancer in the world. Emerging evidence suggests that circular RNAs (circRNAs) participate in the progression of OSCC. However, the role of circ_0000140 in OSCC is still unknown. Methods: The expression of circ_0000140 and microRNA-182-5p (miR-182-5p) were assessed by quantitative realtime polymerase chain reaction (qRT-PCR). Also, cell proliferation, migration and invasion were measured by colony formation and transwell assays, respectively. West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Here, we investigated the role of circ-KIAA0907 in OSCC. Consistent with previous study results [ 16 , 17 ], we confirmed that circ-KIAA0907 inhibited migration, invasion, glycolysis, and facilitated apoptosis of OSCC cells in vitro and OSCC tumor growth in vivo. Moreover, we also proposed that circ-KIAA0907 had an important positive regulatory effect on the radiosensitivity of OSCC cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Here, we investigated the role of circ-KIAA0907 in OSCC. Consistent with previous study results [ 16 , 17 ], we confirmed that circ-KIAA0907 inhibited migration, invasion, glycolysis, and facilitated apoptosis of OSCC cells in vitro and OSCC tumor growth in vivo. Moreover, we also proposed that circ-KIAA0907 had an important positive regulatory effect on the radiosensitivity of OSCC cells.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to this report, our study suggested that miR-96-5p was upregulated in OSCC and it also played the pro-metastasis role in OSCC. Consistent with the previous methods [ 16 , 17 ], the rescue experiments also were performed and the results showed that miR-96-5p reversed the inhibitory effect of circ-KIAA0907 on OSCC progression, indicating that miR-96-5p had a positively regulation on OSCC glycolysis, and had a negatively regulation on OSCC apoptosis and radiosensitivity. These results are a new finding, showing that circ-KIAA0907 targets miR-96-5p, a cancer-promoter, to hinder the progression of OSCC.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“… 27 Intriguingly, circ_0000140 has been identified as a tumor suppressor circRNA in oral squamous cell carcinoma by upregulating CDC73 via sequestration of miR-182-5p. 28 Furthermore, silencing of CDC73 could negate the suppressive effects of oe-circ_0000629 on cell migration, invasion, and proliferation of BC in our study. Basis on these findings, we exhibited that circ_0000629 serves as a miRNA sponge to restrain the BC development through the circ_0000629/miR-1290/CDC73 axis.…”
Section: Discussionsupporting
confidence: 49%